Návrh zdokonalení marketingového mixu společnosti - Hryshchenko, Valeriia (Vysoké učení technické v Brně. Fakulta podnikatelská, 2022)
Bakalářská práce je zaměřena na marketingový mix společnosti PJSC “Poltava Medical Glass Factory”. Teoretická část je zaměřena na teoretická východiska a poznatky marketingového mixu. Analytická část obsahuje rozbor a zhodnocení již stávajícího marketingového mixu. V závěru práce jsou navrhnuta řešení pro zlepšení již zavedeného marketingového mixu, který povede nejen k nalezení nových potencionálních a věrných zákazníku ale především k posílení jména společnosti a tvorbě zisku.

Bachelor thesis is focused on the marketing mix of the company PJSC “Poltava Medical Glass Factory”. The theoretical part is focused on theoretical background and knowledge of the marketing mix. The practical part contains an analysis and assessment of the already existing marketing mix. The conclusion suggested solutions to improve the already established marketing mix that will lead not only to find new potential and loyal customers but also to strengthen the company's name and making a profit.
Proposal to improve the marketing mix of the company
Keywords: marketing; marketingový mix; produkt; cena; zákazníci; propagace; distribuce; marketing; marketing mix; product; price; costumers; promotion; distribution